(3HQfGeL bGFe Ydi LOGhd GdfTGW GdeUhQI dJfejI egGQGJ GdSdGeI hGdCeGf ddCWaGd GdPGJhjjf (B/ s - (3fgi HgfSj aDGO YHOGdbGOQ CHhRjOs; (3SejQI CHhGdMSf YHOGdSdGe (B: s; (3eMeO GdSjO UOjb (B: s ((3GdbGgQI (B: s (3fgi HgfSj aDGO YHOGdbGOQ CHhRjO (B: s, 2015)
(3Jcef CgejI egGQGJ GdSdGeI hGdCeGf aj CfgG JSGYO Ydi JfejI hYi GdWad GdPGJhi HbhGYO MeGjI GdPGJ GdTNUjI hJYQjag HeUGOQ GdNWQ GdJj bO jJYQV dgG aj GdehGba GdMjGJjI GdeNJdaI(B: (3hJeKdJ egGQGJ GdSdGeI hGdCeGf GdeJVefI aj GdOQGSI(B: (3aj egGQGJ GdSdGeI hGdCeGf aj GdefRd(B: (3hegGQGJ GdSdGeI hGdCeGf GdTNUj (B: (3hegGQGJ GdSdGeI hGdCeGf aj GdeLJeY (B: (3hdCf GdUhQ gj GddZI GdChdi dOi GdCWaGd Phi GVWQGH GdPGJhjI GdPjf jYGfhf ef bUhQ MGO aj GdEOQGc hdjSJ GdcdeGJ(B: (3aGf ESJQGJjLjI LOGhd GdfTGW GdeUhQIhGdeYJeOI aj CSGS JUejegG Ydi GdUhQ dELQGA GdCfTWI GdeSJgOaI aj JJGHY efGSH hPdc hab NWhGJ ELQGFjI hefgLjI efXeI ef NdGd JfajP GdGfTWg GdJj JVefgG GdUhQ GdeQabI OGNd GdLOhd(B: (3gj ef CfSH GdGSJQGJjLjGJ GdeSJNOeI eY GdCWaGd GdPGJhjjf s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe GdJQHjI GdNGUIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCWaGd GdPGJhjjfs; (3JfejI egGQGJ GdSdGeI h GdCeGfs; (3LOGhd GdfTGW GdeUhQIs